PERBEDAAN PERUBAHAN WARNA RESIN KOMPOSIT NANOFILLER YANG DIPOLES DAN TIDAK DIPOLES PADA PERENDAMAN LARUTAN TEH HIJAU - Aulia Rusmayati; Isyana Erlita; Muhammad Yanuar Ichrom Nahzi (FKG Unlam, 2017)
ABSTRACTBackground: One of composite resin kinds isoftenused for tooth restoration,it is nanofilled composite resin. Nanofilled composite resin has one major problem which is color change due to external and internal factors. Finishing and polishing are factors that determine color change and together with consumption of colored beverages in a long period of time, it can cause more significant color change. Green Tea is an herbal tea which is often consumed by people nowadays because it has many benefits. However, composition of green tea can also make restoration to change color. Purpose: Theaim of this research was to know the difference of color change between polished and non polished nanofilled composite resin immersed in greentea solutions. Method: This research was a true experimental research with pretest dan post test with control group design using disc samples with diameter of 10 mm and 2 mm thick divided into 4 groups of treatment which were polished nanofilled composite resin group, non polished group, greentea group, and sterile aquadest group. The samples were immersed in different media for 24 hours per day for 5 days. Color change at each group were measured with optical spectrometer (OPT 101 type of photo detector) and digital microvolt. Statistical tests usedpaired T-test and single T-test with a significance of 0.05. Result: Result of this research showed that there were differences in color change on polished nanofilled composite resin and non polished nanofilled composite resin after being immersed in green tea solutions and sterile aquadest.Keywords: nanofilled composite resin, color change, green tea.